Internal Marketing Activities in Educational Hospitals of Yazd, Iran - Shekoofeh Sadat Momahhed; Mohammad Amin Bahrami; Omid Barati; Maryam Moeini (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Internal marketing is defined as "the process of attracting, developing, motivating, and retaining the qualified employees through job-products that satisfy their needs". Internal marketing practices in hospital make a positive work environment, which in turn, leads to the provision of higher care quality. This study was aimed to investigate the internal marketing practices in two educational hospitals of Yazd City, Iran Methods: In this quantitative cross-sectional study, we used a valid questionnaire of internal marketing (Sarah May Lubbe, 2013) in two educational hospitals of Yazd, Iran. A total of 156 clinical and non-clinical employees selected from the studied hospitals participated in the study. Stratified random sampling method was applied and data analysis was done using SPSS19. We used descriptive statistics in data analyses. Results: The mean score of internal marketing was 2.78 ± 0.60. Furthermore, employee satisfaction and benchmarking obtained the highest and lowest scores among the internal marketing dimensions with 3.22 ± 0.64 and 2.27 ± 0.86 scores, respectively. Conclusion: Our results showed the weakness of internal marketing practices in educational hospitals, which should be improved. For this, the results of our study should be prioritized to improve the activities.